MINING SYSTEMS WITH SHRINKAGE STOPING AND THE FORMATION OF ARTIFICIAL PILLARS TO SUPPORT UNSTABLE ROCKS OF VEIN DEPOSITS - Raimzhanov B. R.; Khakimov Sh. I; Khamzaev S.A; Ravshanov A. A (Galaxy International Interdisciplinary Research Journal, 2021)
The characteristic of the occurrence of ore bodies of the Zarmitan gold ore zone, the Navoi Mining and Metallurgical Combine (NMMC) is given. The results of the analysis of the systems used for the mining of steeply-falling vein deposits with insufficiently stable host rocks are presented. For the mining of vein deposits with a capacity of up to 2.0 m in unstable massifs, variants of a system with the stock of broken ore in combination with a spacer (spacer-frame) and metal rod support, variants with short or narrow shrinkage, with intervening and interfloor pillars are considered. The main disadvantages of the development systems applied in unstable massifs and complex geomechanical conditions are given, which include the consumption of expensive materials, labor costs, a significant increase in the volume of preparatory and cutting operations and the loss of ore in the pillars. Variants of systems are proposed for the development of ore with an open cleaning space for the development of reserves of weakly stable massifs and in zones of stress concentration, providing for combined methods of managing a rock mass with stock of broken ore, ore pillars and hardening backfill, which makes it possible to gradually develop both chamber reserves and pillar reserves.